Social Work as Laboratory for Normative Professionalisation - Harry Kunnemann (Social Work & Society, 2005)
In most Western countries, the professional status of social workers is instable and insecure. Of course, most Western countries are themselves instable, ridden with feelings of insecurity and in search of reassurance and promises of control. But social work hardly lends itself as a projection screen for visions of professional control and efficiency in the face of insecurity. On the contrary: within the present cultural and political climate, social work connotes primarily with unpopular social problems, with people unable to cope adequately with the competitiveness and the rate of change of post-industrial societies, that is to say: it connotes more with dependency and helplessness then with autonomy and control. Moreover, whereas public discourse in most Western country is dominated by a neo-liberal perspective and the intricate network of economic, managerial, consumerist and military metaphors connected with it, social work still carries with it a legacy of 'progressive politics' increasingly labeled as outdated and inadequate. Although the values of solidarity and social justice connected with this 'progressive heritage' certainly have not faded away completely, the loudest and most popular voices on the level of public discourse keep underscoring the necessity to adapt to the 'realities' of present-day postindustrial societies and their dependence on economic growth, technological innovation and the dynamics of an ever more competitive world-market. This 'unavoidable' adaptation involves both the 'modernization' and progressive diminishment of 'costly' welfare-state arrangements and a radical reorientation of social work as a profession. Instead of furthering the dependency of clients in the name of solidarity, social workers should stimulate them to face their own responsibilities and help them to function more adequately in a world where individual autonomy and economic progress are dominant values. This shift has far-reaching consequences for the organization of the work itself. Efficiency and transparency are the new code words, professional autonomy is dramatically limited and interventions of social workers are increasingly bound to 'objective' standards of success and cost-effectiveness.